Investigating Relevant Data in Automotive Procurement Departments: External Shocks as Transparency Creator for Data Deficits in Decision-Making - Sven Klee; Andreas Janson (Information Systems Frontiers, 2023)
Uncertainty becomes the new normal for organizations worldwide. Many organizations are dependent on complex global supply chains. COVID-19, but also environmental disasters or the war in Ukraine, demonstrate the volatility of supply chains. Procurement departments are the central interface between internal and external stakeholders and must manage the supply chain stability what requires fast and accurate decision-making. External shocks and sudden disruptions of central supply chains illustrated that data analytics could not prevent disruptions, although sound research on competitive advantages and numerous investments should have enabled organizations to data-driven decision-making. Rather, it became transparent, that there are numerous data deficits in organizations. We did an interview-based study with 23 procurement and supply chain experts about relevant data sets and the status of its usability. We contribute to theory and practice by uncovering relevant aspects of data and provide theoretical propositions on how decision-making can be improved in automotive procurement departments.
Keywords: 000; Data analytics; Decision-making; Procurement departments; Supply chain; Automotive manufacturers; External shocks